Oncolytic virotherapy in veterinary medicine: current status and future prospects for canine patients - Patil, Sandeep S (BioMed Central, 2012)
Oncolytic viruses refer to those that are able to eliminate malignancies by direct targeting and lysis of cancer cells, leaving non-cancerous tissues unharmed. Several oncolytic viruses including adenovirus strains, canine distemper virus and vaccinia virus strains have been used for canine cancer therapy in preclinical studies. However, in contrast to human studies, clinical trials with oncolytic viruses for canine cancer patients have not been reported. An 'ideal' virus has yet to be identified. This review is focused on the prospective use of oncolytic viruses in the treatment of canine tumors - a knowledge that will undoubtedly contribute to the development of oncolytic viral agents for canine cancer therapy in the future.